1999
DOI: 10.1002/(sici)1099-1646(199901/06)15:1/3<43::aid-rrr535>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of riverine plants to flooding and exposure indicated by water regime

Abstract: Selected water regime indices are used to describe the tolerances to flooding and exposure of littoral and floodplain plants of the River Murray, South Australia. The cover and abundance of 26 perennial species were surveyed at 12 sites along a reach where water levels were influenced by weir operations. Six indices were measured: days when water depths were ≥0, 0–20, 20–60 and ≥200 cm; days when plants were exposed to ≥100 cm of water; and days of longest exposure to water. Ordinations of plant abundances wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 806 publications
(51 citation statements)
references
References 37 publications
(43 reference statements)
3
48
0
Order By: Relevance
“…Bermudagrass is reportedly capable of tolerating prolonged periods of complete submersion (Blanch et al, 1999). Therefore, it is not surprising that bermudagrass performed well under saturated conditions for the 72-day period of this study.…”
Section: Effect Of Soil Saturation On 15 N-nitrate Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…Bermudagrass is reportedly capable of tolerating prolonged periods of complete submersion (Blanch et al, 1999). Therefore, it is not surprising that bermudagrass performed well under saturated conditions for the 72-day period of this study.…”
Section: Effect Of Soil Saturation On 15 N-nitrate Uptakementioning
confidence: 99%
“…turfgrasses are widely planted in the southeastern U.S. While there are few published data, bermudagrass is considered to possess tolerance to a wide range of conditions including submergence (Rhoades, 1964;Blanch et al, 1999), while centipedegrass may lack tolerance to saturated soils (Horn, 1966;Beard, 1973;Turgeon, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The water-level variation can affect the establishment, growth, and survival of aquatic plants (Blanch et al 1999;Seabloom et al 2001). The variation in wetland vegetation is driven by changes in aquatic macrophyte populations whose response to hydrological oscillation can occur in several ways (van der Valk 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Because hydrologists are not concerned directly with when such extreme events occur, standard hydrological statistics are often not relevant to ecologists because they are not linked to ecologically important phenomena like seed dispersal, seed germination, seedling growth and survival, etc. Duration of flooding has been the most common hydrological statistic used to explain the distribution of species in wetlands (e.g., Nestler & Long, 1997;Toner & Keddy, 1997;Blanch et al, 1999). Richter et al (1996), however, suggested a series of hydrological statistics or 'Indicators of Hydrologic Alteration' that can be used to describe the hydrology of, and to assess hydrologic alterations to, aquatic ecosystems.…”
Section: Hydrological Statisticsmentioning
confidence: 99%